2008
DOI: 10.3390/molecules13092249
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Various Drugs on Alcohol-induced Oxidative Stress in the Liver

Abstract: The major aim of this work was to investigate how alcohol-induced oxidative stress in combined chemotherapy changes the metabolic function of the liver in experimental animals. This research was conducted to establish how bromocriptine, haloperidol and azithromycin, applied to the experimental model, affected the antioxidative status of the liver. The following parameters were determined: reduced glutathione, activities of glutathione peroxidase, glutathione reductase, peroxidase, catalase, xanthine oxidase an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 28 publications
(29 reference statements)
2
9
0
Order By: Relevance
“…However, SOD and CAT activities were increased by CCl 4 , in contrast to GSP and GR. Several studies have found a decreased antioxidant enzymes expression following CCl 4 administration [57,58], others, including the current study, found increased levels after CCl 4 challenge [59][60][61]. One probable cause of this increase was suggested to be the high free radical challenge that the enzymes encounter, leading to their overexpression [62].…”
Section: Discussionsupporting
confidence: 47%
“…However, SOD and CAT activities were increased by CCl 4 , in contrast to GSP and GR. Several studies have found a decreased antioxidant enzymes expression following CCl 4 administration [57,58], others, including the current study, found increased levels after CCl 4 challenge [59][60][61]. One probable cause of this increase was suggested to be the high free radical challenge that the enzymes encounter, leading to their overexpression [62].…”
Section: Discussionsupporting
confidence: 47%
“…Hepatic toxicity of the antipsychotic HP has been reported in cultured rat hepatocytes 26 and experimentally in Wistar rats. 27,28 Shivakumar et al (1992) reported that HP blockade of dopamine receptor increases dopamine turnover resulting in excessive production of hydrogen peroxide and, thus, generates oxidative stress. 17 Haloperidol-induced oxidative stress was associated with an increased generation of brain NO which is a free radical which can be deleterious to brain functions, where synthesis of inducible nitric oxide synthase contributes to the activation of apoptotic pathways in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol is metabolized by three pathways which utilize alcohol dehydrogenase, the microsomal ethanol oxidative system (MEOS) and catalase, respectively [35]. MEOS, characterized by CYP2E1, is viewed as the main site of ROS overproduction during alcohol metabolism.…”
Section: Discussionmentioning
confidence: 99%